Evaluation of antimycobacterial and anticonvulsant activities of new 1-(4-fluorobenzoyl)-4-substituted-thiosemicarbazide and 5-(4-fluorophenyl)-4-substituted-2,4-dihydro-3H-1,2,4-triazole-3-thione derivatives - (:unkn) unknown (ELSEVIER SCIENCE SA, 1997)
Some new 1-(4-fluorobenzoyl)-4-alkyl/arylthiosemicarbazide (2a-g), 5-(4-fluorophenyl)4-alkyl/aryl-2,4-dihydr-3H 1,2,4-triazole-3-thione (3a-g) derivatives, 3-(benzylthio)-5-(4-fluorophenyl)-4-phenyl-4H-1,2,4-triazole (3h) and 2-acetyl-5-(4-fluorophenyl)-4-phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione (3i) were prepared and tested for their antimycobacterial and anticonvulsant activities. The structure of compounds was confirmed by elemental analyses and spectroscopic techniques. The antimycobacterial activity of the synthesized compounds was investigated against M. fortiutum ATCC 6841 and most of them were found active against the above strain with MIC values of 64 or 32 mu g/ml. The anticonvulsant activity of the 2d, 3d-i was determined against pentylenetetrazole induced seizures. 3f-i showed anticonvulsant activity (10 to 30% protection).
Keywords: ANTIFUNGAL ACTIVITIES; ANTIBACTERIAL; AGENTS